A Modern Pilgrim in Mecca and a Siege in Sanaa - Daniel Martin Varisco (International Institute of Islamic Thought, 2007)
It should be noted that the trespassing English pilgrim Arthur Wavell is definitely not postmodern; his “modern” account of a trip in disguise to Makkah and Madinah was originally published in 1912. The author revels in explaining how he pulled off the role of a Zanzibar Muslim on hajj, as though he is presenting a how-to guide for fellow swashbucklers. Previously, he had carried out intelligence work for the British Army in South Africa and, in 1906, settled on a farm near Mombasa, where he learned Arabic and met Muslims. He died at the young age of thirty-four while fighting in East Africa. Wavell presents a riveting tale with a self-serving hubris that could easily be dismissed as a remake of Sir Richard Burton’s earlier and more celebrated penetration of Makkah. But there is good reason to read this dated book, if only for the historical view of travel to Makkah near the end of the Ottoman caliphate. Wavell traveled from Damascus on the Hijaz railway the very year (1908) that it reached Makkah. His trip was made partly out of curiosity, no doubt fueled by the fact non-Muslims are forbidden to enter ...